Elucidating metabolites and biosynthetic pathways during musk maturation: insights from forest musk deer - Jie, Hang; Li, Feng; Liu, Qian; Zheng, Tingting; Tan, Helin; Feng, Xiaolan; Zhao, Guijun; Zeng, Dejun; Li, Diyan; Xu, Zhongxian; Wang, Tao (Frontiers in Pharmacology, 2025)
BackgroundMusk is a blackish-brown solid used in traditional Chinese medicine with a unique and intense scent. Limited evidence on its function and pathways is available from databases due to the complexity, variability, and derivativity of chemical composition.ResultsIn this study, musk samples from three different stages during maturation: the end of June (group A), August (group B), and October (group C) were harvested from six male forest musk deer. A gas chromatography and mass spectrometry (GC-MS) approach was used to explore the chemical composition. Results indicated the presence of 66 known and 14 unknown chemicals, including 29 aromatic compounds. Lipids (51.52%), organic oxygen compounds (28.79%), and organoheterocyclic compounds (12.12%) were the most abundant substances. A total of 13 differential metabolites were found, including four macrocyclic ketones and six androgens and derivatives that increased as musk matured. Biosynthesis of unsaturated fatty acids was enriched in differential metabolites across stages. Tetracosanoic acid, methyl ester, and TES1 [EC: 3.1.2.2] participated in the biosynthesis of muscone. A total of nine chemicals and six steroidogenic enzymes participated in steroid hormone biosynthesis.ConclusionThis study annotates and defines metabolites in musk systematically, macrocyclic ketones (9.09%) and lipids (51.52%) were categorized unambiguously, suggesting that previous studies have underestimated the lipid content in musk, and critical role for lipid metabolism in musk gland development and odor profile formation. The high lipid content may reflect energy storage for glandular activity or serve as precursors for volatile compound synthesis, offering new mechanistic insights into musk maturation. Therefore, we preliminarily decipher the biosynthetic pathways of muscone and steroids through providing involved enzymes and metabolites. These results will deepen the understanding of the composition of natural musk and offer new theoretical insights to promote the comprehensive use of this resource.